Clinical and radiological correlation of pulmonary manifestations in rheumatoid arthritis - Srilakshmi M Prabhu; Ram Shenoy Basti (Asian Journal of Medical Sciences, 2024)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory arthritis with various extra-articular manifestations, pulmonary being the most involved. Aims and Objectives: This study aims to identify the radiological patterns in the lungs among patients with RA. Materials and Methods: A total of 39 patients with RA were chosen randomly. They were examined and imaged by chest X-ray and high-resolution computed tomography (HRCT) thorax, and findings were analyzed. Results: The mean age of patients was 53.9 and had a female preponderance of 74.4%. Among the 39 patients studied, 30 had no respiratory symptoms. The most common HRCT thorax findings were bronchiectasis and ground-glass opacities. Conclusion: Radiological pulmonary manifestations of RA identified in HRCT imaging are wide and occur in the majority of clinically asymptomatic patients.